MyGift programme: an initiative to generate income - Hazlina, Faizal (Penerbit UMP, 2015)
The endowment fund or wakaf is a form of fund channelled by individuals or private companies that are interested in making financial contribution to institutes of higher learning and is meant for the development of education. The contribution can be utilised for education development activities that received collective approval.